Framing of Online News Media Regarding the Constitutional Court's Decision - Reza, Faisal; Pafritasary, Getse; Putri, Shinta Hartini; Lathifah, Nisa (Sinergi International Journal of Communication Sciences, 2024)
This study examines how Detik.com and Kompas.com frame news coverage of the Constitutional Court’s decision on Article 169 letter q of Law No. 7 of 2017, which allows presidential and vice-presidential candidates to be at least 40 years old or have previously held an elected position. The decision, issued in October 2023, sparked public debate regarding youth involvement in politics and constitutional consistency. Employing a qualitative method with a framing analysis approach, data collection was conducted through purposive sampling, observation, documentation, and interviews. The results reveal contrasting framing strategies between the two media outlets. Detik.com frames the decision positively, viewing it as a progressive step to encourage youth participation in national politics. In the problem definition element, Detik.com highlights the benefits for young generations, while Kompas.com frames it as controversial, emphasizing its potential to undermine legal stability. In diagnosing causes, Detik.com attributes the ruling to efforts to empower younger politicians, whereas Kompas.com identifies inconsistencies within the Constitutional Court as the root issue. For moral judgment, Detik.com regards the decision as momentum for youth political consolidation, while Kompas.com criticizes its adverse constitutional implications despite acknowledging its finality. In treatment recommendation, Detik.com suggests eliminating discrimination against youth in politics based on merit, while Kompas.com recommends rejecting the ruling to prevent further complications. This study concludes that media framing significantly shapes public perception, with Detik.com and Kompas.com reflecting differing editorial stances. The findings emphasize the crucial role of balanced, objective reporting in fostering an informed public discourse on political decisions.